Determination of Debt Use on Capital Structure in Indonesia - Tasrim Tasrim; Vebby Anwar; Estiani Estiani; Angga Kurniawan; Ansri Jayanti (Universitas Muhammadiyah Yogyakarta, 2024)
The use of debt is a strategic decision of the company. The company must make such decisions for the sustainability of its operations. The study investigates the factors influencing debt use in a company's capital structure. The locus of research was a technology business registered on the Indonesia Stock Exchange. The sampling was of 17 companies selected through the purposive sampling method. The companies selected as research samples were those that routinely reported financial statements during the research period from 2019 to 2023. Multiple regression analysis was employed to analyze the data. The results showed that liquidity strength negatively correlated with debt use, while the Current Ratio (CR) did not show a significant effect. Tangible assets affect the debt-to-equity ratio (DER), and no significant effect was found on the use of STDTA. Return on Asset (ROA) negatively affects short total debt to total assets (STDTA) and positively affects DER. In contrast, Total Asset Turnover (ATO) and Return on Equity (ROE) positively affected STDTA. ATO had a negative impact on DER. Meanwhile, ROE was not found to have a significant effect on DER. The company uses the pecking order theory approach in its capital structure policy. It pays more attention to internal conditions before adopting a policy of using or increasing debt in the capital structure.